The Influence of Human Resources on Satisfaction with Nasionaol Health Insurance Services with Service Quality as A Mediating Variable - Arghi Charisma Putri; Sulis Diana; Arief Fardiansyah (GLOBAL HEALTH SCIENCE GROUP, 2025)
Service satisfaction is one of the key indicators of successful healthcare service delivery to the community. Community Health Centers (Puskesmas) serve as the backbone of primary healthcare services and are expected to maintain service quality consistently. This study aims to analyze the factors influencing the satisfaction of participants in the National Health Insurance (JKN) program with the services provided at primary care facilities (FKTP) in Puskesmas Balen, with service quality as a mediating variable. The research was conducted at Puskesmas Balen, Bojonegoro Regency, using a quantitative approach. The independent variables include JKN membership type, participant knowledge, physical facilities, equipment and supplies, and human resources (HR). The dependent variable is FKTP service satisfaction, with service quality as the mediating variable. A total of 324 respondents were selected using the Slovin formula and simple random sampling technique. Data were collected using a structured questionnaire based on Guttman and Likert scales, and analyzed using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) approach. The model validity results using loading factor values greater than 0.7 are considered acceptable, with an R2 value of 9.4% being considered weak. Meanwhile, the reliability test is seen from the Composite Reliability (CR) value of 0.946 more than or equal to 0.70 (very good), Cronbach's alpha (CA) 0.939 more than or equal to 0.90 (very good) and Average variance extracted (AVE) 0.647 more than or equal to 0.50 (Valid). The results showed that contribution assistance recipients (CAR) tended to have significantly lower satisfaction levels compared to non-PBI participants signifikan (P Value=0,000 <0,05 ; T statistics 5.082 >1,96). Knowledge (P Value=0,000; T statistics 5.082), physical facilities (P Value=0,000; T statistics 10,749), and HR (P Value=0,000; T statistics 10,539) had a positive and significant influence on service satisfaction. Equipment and supplies showed a negative and insignificant effect (P Value=0,077 > 0,05; T statistics -0,249 <1,96). Joint testing indicated that only human resources had a strong and significant positive influence on FKTP service satisfaction, both directly and indirectly through the mediating role of service quality. Service quality functioned as a partial mediator parsial (P Value=0,000, T statistics 0,336, VAF 26%). Therefore, improving human resources not only directly impacts satisfaction but also enhances the overall perception of service quality, ultimately increasing user satisfaction.